Pengenalan Permainan Warna Melalui Konsep Senyawa Polar dan Non Polar - Nazarullail, Fikri; Rendy, Dwi Bagus (Institut Agama Islam Negeri Ponorogo, 2021)
Introduction to Color Games Through the Concept of Polar and Non Polar Compounds. This research was conducted to provide a new learning experience by adapting the concept of color recognition combined with simple science (polar and non polar). This study uses quantitative research approach with one-shot case study type. The results of a simple experimental process conducted in the learning process get positive data that is 88% or 15 children get a very good score and 12% or 2 children get a good score. Based on these results, similar activities can be carried out to introduce children to the concept of mixing colors adapting simple science in learning activities.